Lead Levels in Blood and Urine, Blood Pressure, and Hemoglobin Levels in Online Motorcycle Taxi Workers in Denpasar - Diah Prihatiningsih; Putu Ayu Parwati; Anak Agung Ayu Eka Cahyani (Postgraduate, University of Mataram, 2026)
This study aimed to analyze the relationship between blood lead (Pb) level, urine Pb level, blood pressure, and hemoglobin level among online motorcycle taxi workers in Denpasar. A quantitative cross-sectional design was used involving 96 drivers selected by purposive sampling. Data were collected through questionnaires, direct physical measurements, and laboratory examinations of blood Pb, urine Pb, and hemoglobin. Normality was tested using the Kolmogorov–Smirnov test. Because several variables were not normally distributed, the data were analyzed using Spearman rank correlation, Mann–Whitney U test, and linear regression. Blood Pb level was not significantly associated with systolic blood pressure, diastolic blood pressure, or hemoglobin level. Urine Pb level was not significantly associated with systolic or diastolic blood pressure, but showed a significant weak negative correlation with hemoglobin level. Blood Pb and urine Pb levels were not significantly correlated. Work duration was not significantly associated with Pb levels, whereas daily working hours showed a marginal association with blood Pb. These findings indicate limited hematological effects and support routine biomonitoring and preventive occupational health measures in traffic-exposed workers.